Conversational Analysis on Adjacency Pairs Occurred in Teaching and Learning English of Intellectual Disability Classroom: A Descriptive Study at a Special Needs School - Dita Etik Setiani (JELLE, 2025)
This research aimed to investigate the most types of adjacency pairs that occurred in the conversation in 12th grade students with intellectual disability. This research also focused on how the teacher used the adjacency pairs on the teaching and learning process in the classroom. Using descriptive qualitative methods, the data were collected by recording the conversation, observation, and teacher interview. The participants of this research are the teacher and the 12th grade students of Special Needs School C and C1 Yakut Purwokerto that consist of 15 students. The findings reveal that 5 types of adjacencies pair out of 11 types occurred: question-answer (51 pairs), greeting-greeting (2 pairs), request-acceptance (3 pairs), assessment-agreement (3 pairs), and leave-taking (1 pair). Among these pairs, question-answer adjacency pairs were the most prevalent, occurring 51 times throughout the conversation. These pairs played a vital role in maintaining student engagement and supporting communication in the classroom. Students with intellectual disability responded to the teacher with preferred answers, which means that they were able to follow the teachers prompts, but they struggled to initiate the conversation first. The analysis further highlights the importance of adjacency pairs used by the teacher in creating a supportive environment in which students can participate more actively.